Efektivitas Media Audio Visual Dalam Meningkatkan Pengetahuan Tentang Seribu Hari Pertama Kehidupan Remaja Putri - Sunaeni Sunaeni; Al Inayah M. Abduh; Mariana Isir (Malahayati Nursing Journal, 2022)
ABSTRACT Understanding nutrition in the first thousand days of human life needs to be promoted in preventing stunting. Adolescent girls have a key role in maintaining health during pregnancy, of which 28.72% of women in West Papua aged 15-19 years (SMP-SMA) are pregnant for the first time. Audio-visual media can be used as an alternative in disseminating information on stunting prevention during the "golden period". The purpose of this study was to determine the effect of audio-visual media on the knowledge of young women about the first thousand days of life. The research methods approach used a quasi-experimental pre-and post-test design. The population is 468 female students. The sampling technique used simple random sampling to get 46 respondents. The data collection instrument used a questionnaire with 34 questions. Data collection was carried out directly on young women before and after being given treatment in the form of counseling using audiovisual. Data analysis used paired T-Test with the help of software at a significance level of 0.05 and presented in the table. The results showed a p-value of 0.001, there was a significant difference in knowledge about the first thousand days of life for young women at MAN Model Sorong before and after being given treatment. Counseling about the first thousand days of life is very important for all young women, cross-sectoral collaboration is needed to produce the next generation that is free from stunting. Keywords: The first thousand days of life; stunting; adolescent girls, audiovisual; media ABSTRAK Pemahaman gizi pada seribu hari pertama kehidupan manusia perlu digalakkan dalam mencegah stunting. Remaja putri memiliki peran kunci dalam menjaga kesehatan selama kehamilan, dimana 28,72% wanita di Papua Barat berusia 15-19 tahun (SMP-SMA) hamil untuk pertama kalinya. Media audio visual dapat digunakan sebagai salah satu alternatif dalam menyebarluaskan informasi pencegahan stunting pada masa “masa emas”. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh media audio visual terhadap pengetahuan remaja putri tentang seribu hari pertama kehidupan. Pendekatan metode penelitian menggunakan quasi-experimental pre-and post-test design. Populasinya adalah 468 mahasiswi. Teknik pengambilan sampel menggunakan simple random sampling dengan jumlah 46 responden. Instrumen pengumpulan data menggunakan kuesioner dengan 34 pertanyaan. Pengumpulan data dilakukan secara langsung pada remaja putri sebelum dan sesudah diberikan treatment berupa penyuluhan menggunakan audiovisual. Analisis data menggunakan Paired T-Test dengan bantuan software pada taraf signifikansi 0,05 dan disajikan dalam tabel. Hasil penelitian menunjukkan p-value 0,001, terdapat perbedaan pengetahuan yang bermakna tentang seribu hari pertama kehidupan remaja putri di MAN Model Sorong sebelum dan sesudah diberikan perlakuan. Penyuluhan tentang seribu hari pertama kehidupan sangat penting bagi semua remaja putri, diperlukan kerjasama lintas sektor untuk menghasilkan generasi penerus bangsa yang bebas stunting. Kata kunci: seribu hari pertama kehidupan, kerdil, gadis remaja, audiovisual, media